Reasonable Education in the Book of Tarbiyatul Aulad by Abdullah Nashih Ulwan and Its Implications in Modern Education - Tri Yugo (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This research aims to explore the concept of intellectual education in the book "Tarbiyatul Aulad" by Abdullah Nashih Ulwan and analyze its relevance to modern education. Abdullah Nashih Ulwan emphasized the importance of intellectual education, which focuses on mastering knowledge and developing critical thinking skills, analytical skills, and the cultivation of ethical and moral values based on Islamic teachings. The educational methods recommended by Ulwan, such as dialogue and discussion, reading habits, active learning, and judicious use of technology, show suitability for modern educational needs that demand a balance between intellectual and moral aspects. This study uses a qualitative method with a descriptive-analytical approach to identify the principles and methods of intellectual education in the book of Ulwan and compares them with the approach in modern education. Data was obtained through a literature review and analysis of the text of the book "Tarbiyatul Aulad". The results of the study show that the concept of intellectual education proposed by Ulwan can be adapted to the modern education system to create a holistic and balanced education. The implementation of these concepts in modern education can face challenges such as resistance to change and limited resources, but the opportunities to improve the quality of education and character development of children are enormous. In conclusion, the education of reason in the book "Tarbiyatul Aulad" significantly contributes to the development of modern education that is more comprehensive, integrative, and based on Islamic values.